Fas gene promoter polymorphisms in primary Sjögren's syndrome. Issue 1 (12th December 2003) - Mullighan, C G; Heatley, S; Lester, S; Rischmueller, M; Gordon, T P; Bardy, P G
Abstract : Background: Fas mediated apoptosis may be important in the pathogenesis of primary Sjögren's syndrome (pSS). Objective: To examine genetic variation in the promoter region of the Fas gene in pSS. Methods: Two single nucleotide polymorphisms at positions −1377(G/A) and −670(G/A) in the Fas gene promoter were genotyped by PCRSSP in 101 patients with pSS and 108 Caucasoid controls. Results: No significant differences in allele or genotype frequencies were detected between the patients with pSS and controls. However, significant associations were observed with Ro/La autoantibody negative patients, who display milder and later onset disease. The −670A allele was more frequent in Ro/La autoantibody negative patients than in Ro/La autoantibody positive patients (p = 0.04). Conclusion: This study does not confirm an earlier report of an association between pSS and the Fas promoter −670G allele. However, the results suggest that genetically determined variability in Fas expression may modulate Ro/La autoantibody responses in patients with pSS.